Association of Race and Risk of Future Scleroderma Renal Crisis at Systemic Sclerosis Diagnosis. Issue 4 (20th December 2022) - Forman, Crystal J.; Olson, Stephen W.; Gordon, Sarah M.; Hughes, James B.; Stitt, Rodger S.; Bailey, Wayne T.; Edison, Jess D.; Nee, Robert
Abstract : Objective: Scleroderma renal crisis (SRC) is a rare and severe manifestation of systemic sclerosis (SSc). Although it is well documented that Black patients with SSc have worse morbidity and mortality than non‐Black patients, racial predilection for SRC is underreported. We examine the association of race and future development of SRC in an SSc cohort. Methods: Using the electronic health record of the US Military Health System, we conducted a comprehensive chart review of each patient with SSc from 2005 to 2016. The final study cohort was comprised of 31 SRC cases and 322 SSc without SRC controls. We conducted logistic regression of SRC as the outcome variable and race (Black versus non‐Black) as the primary predictor variable, adjusted for age, estimated glomerular filtration rate, hypertension, and proteinuria at SSc diagnosis. Results: Of 353 patients, 294 had identifiable race (79 Black, 215 non‐Black). Thirteen of 79 Black patients (16.5%) versus 16 of 215 (7.4%) non‐Black patients developed SRC ( P = 0.02). On adjusted analysis, Black patients had a significantly higher risk of developing SRC than non‐Black patients (odds ratio 6.4 [95% confidence interval 1.3–31.2], P = 0.02). Anti‐Ro antibody was present in a higher proportion of Black SRC patients versus Black patients without SRC (45% versus 14%, P = 0.01). Conversely, older age, thrombocytopenia, and anti‐RNA polymerase III antibody at SSc diagnosis were significantly associated with future SRC in the non‐Black cohort. Conclusion: Black race was independently associated with a higher risk of future SRC. Further studies are needed to elucidate the mechanisms that underlie this important association.